Stress Among Working Women: Counselling Services Using the Lazarus Stress Theory and the Practice of Solution-Focused Therapy - Nurul Naimah Rose; Mohd Yusri Mustafa (Asian Social Work Journal, 2018)
This paper aims to understand the stress among working women and helping method that can be used by counseling practitioners through the concept of Lazarus Stress Theory and Solution-focused Therapy application. The Focused issue is the stress among working women. Stress is an issue that often occurs to women working due to factors such as work load, health problems, childcare, social relations, relationships with spouses, time management and self-care. Although there are various methods that can be used to help them reduce the level of stress, it still can not be resolved properly. In fact, it continues to effect women's emotions and their quality of life. The adverse effects of stress can be identified based on four aspects namely physical, emotional, behavior and thinking. Therefore, it is important for counseling practitioners to help women to manage their stress. The application of the concept of Lazarus Stress Theory in counseling sessions is important as a guide to counselors in understanding the factors, effects, and situations that are happening to the client. Based on Lazarus's Theory, stress can be understood through three aspects, namely the stimulus, the respond and the process. After getting a clear understanding of the issue, counselors can apply specific techniques in Solution-Focused Therapy such as scaling techniques and miracle questions to help clients. The combination of understanding theoretical concepts and application of therapeutic techniques enhances counseling services as well as demonstrating professionalism of counselors in carrying out their duties.